Friction of Si3N4 Ball / Si3N4 Disk Sliding in Water with SiO2 Nano-particles - Kosuke Ito (Japanese Society of Tribologists, 2006)
Silica nano-particles that have the average diameter of 7 nm were added to water, and their effects on friction were studied for Si3N4 self-mated sliding couples by a ball-on-disk tribotester under boundary lubricated conditions. By adding 0.01 or 0.1 wt % of silica particles to water, the running-in distance was reduced significantly in both cases at the sliding velocity of 0.21 m/s and resulted in low and stable friction (μ 0.05) under low velocity conditions (v ≤ 0.12 m/s). The optimum concentration of the silica for the low and stable friction was 0.01 wt % among those tested in this study, which is the closest to the solubility limit of silica to water.